2020
DOI: 10.30534/ijatcse/2020/48912020
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Neural Network based on MIMO and Channel Estimation for Impulsive Noise Environment in Mobile Wireless Networks

Abstract: Multiple Input Multiple Output (MIMO) system has several input and output antennas for executing the data transmission. Channel Estimation (CE) is required in MIMO, to achieve the effective signal transmission over the various amount of antennas in mobile networks. By using CE over the MIMO, the noiseless data transmission is performed. Hence in this paper, a Multi layer Neural Network (MNN) is used for identifying the CE and this system is named as Multi-layer Neural Network-MIMO-Digital Filter (MNN-MIMO-CE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The 5G networks are designed to support intelligent IoMT-based medical applications that require high data throughput, scalability, blockchain rollout, low latency, dense deployment, reliability, high energy efficiency, and long-term communication. Figure 3 shows the fogIoMT Architecture for the security of IoT device-based healthcare records using blockchain technology [42][43][44].…”
Section: The 5g Technology and Its Applicationsmentioning
confidence: 99%
“…The 5G networks are designed to support intelligent IoMT-based medical applications that require high data throughput, scalability, blockchain rollout, low latency, dense deployment, reliability, high energy efficiency, and long-term communication. Figure 3 shows the fogIoMT Architecture for the security of IoT device-based healthcare records using blockchain technology [42][43][44].…”
Section: The 5g Technology and Its Applicationsmentioning
confidence: 99%
“…Consequently, most organizations need to invest in cybersecurity and employee training to raise awareness of the importance of securing systems and their sensitive information [12]. One approach to protecting information systems was suggested by [13], which suggested that integrating information systems across organizational environments can improve cybersecurity. The researchers suggested and tested three hypotheses to investigate whether integration is positively related to cybersecurity countermeasures (see Table I).…”
Section: Cybersecuritymentioning
confidence: 99%
“…• Most of the mentioned schemes are having a complex cryptographic process that minimizes the performance of the network. 17,21 • Most of the existing schemes are complex in real-time implementation 19,22 • Some of the mentioned schemes are effective against load balancing but they reduce the network performance, which minimizes their usage in the real-time scenario. 15,23 The proposed solution in this article considers defending and attacking the network from the perspectives of evolutionary games.…”
Section: Limitations Of Wsnmentioning
confidence: 99%